(untitled) (SCIENCE TIME JOURNAL, 2026)
This study focuses on how to use real-life materials in classes where students have different language levels. It explores several ways of making lessons more engaging and easier to understand. The study finds that breaking tasks into steps and providing appropriate support help students improve their understanding and active participation regardless of their language proficiency level. Based on task-based research, the study highlights effective strategies of implementing authentic materials. It focuses on two strategies: task-based adaptation and scaffolding. These strategies improve student performance and make lessons more accessible and fun. They help students with English levels understand and participate. The study shows that using real-life materials and adapting tasks can improve learning. The findings are based on classroom research. They show that adapting materials and providing support are key. These approaches help students learn English better. They make lessons more engaging and fun for students, with skill levels.